2016
DOI: 10.1080/15022250.2015.1137487
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Terror - About the Effect of Different Kinds of Terror on Risk Perceptions

Abstract: Terrorism is an increasing problem; still, research systematically investigating the impact of varying kinds of terrorism is scarce. The present investigation uses hypothetical scenarios to look at effects of diverging sorts of terrorism on risk perceptions in a student-and a tourist sample. Two characteristics of terrorism were varied systematically: frequency (whether terrorism hits a destination where terrorism is frequent or infrequent) and degree of organization (whether terrorism is committed by an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
3
20
0
3
Order By: Relevance
“…Larsen, Brun and Øgaard (2009) found that potential tourists (i.e., students) reported higher travel related worries regarding a number of hazards including terrorism compared to traveling tourists. Similar findings are reported by Wolff and Larsen (), who found higher terror risk estimates, which were not explained by age differences, in students then in tourists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsen, Brun and Øgaard (2009) found that potential tourists (i.e., students) reported higher travel related worries regarding a number of hazards including terrorism compared to traveling tourists. Similar findings are reported by Wolff and Larsen (), who found higher terror risk estimates, which were not explained by age differences, in students then in tourists.…”
Section: Discussionmentioning
confidence: 99%
“…They found that risk judgments remained low and constant for several years before the massacre, while a slight but significant decrease in perceived risk for Norway as a destination was observed the year following the attack. While discussing possible explanations the authors speculated whether this counterintuitive finding might be caused by the gamblers fallacy (Tversky & Kahneman, , ) and in fact the authors (Wolff & Larsen, ) do report some partial support for this assumption.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting line of research with growing importance is loosely linked to behavioural economics and dominated by psychologists. These strands studies of the behaviour, beliefs and intentions of tourists and include studies like Doran et al (2017), Brun et al (2011), Larsen et al (2011), Larsen (2011) as well as Wolff and Larsen (2017). The study by Larsen (2007) seems to be fundamental for this research field, which, among other things, is important for the analysis of how terror and risk perceptions influence the travel intentions of tourists.…”
Section: Current State Of Tourism Economics Research In a Nordic Contextmentioning
confidence: 99%
“…Since tourism demand and tourism supply are closely linked, it is logical to assume that if terrorism does not significantly affect the decline in tourist arrivals, there will be no downturn in tourism supply, i.e., FDI in tourism will not decline. The arguments in favour of the set hypothesis are as follows: according to the latest research, tourists are not too concerned about terrorism [12,77,78], after the terrorist attack, tourism had already been recovering for 13 months [23], the latest UNWTO data show a continuous growth rate of international tourist arrivals [2], less significant and limited terrorist attacks have little impact on the expected returns of an investment project [33], out of 39 sectors, tourism is ranked 10th in terms of capital investment [79] and, above all, FDI in tourism continues to enter the countries affected by terrorism [80]. Market size is generally the most important determinant of FDI inflows.…”
Section: Hypothesismentioning
confidence: 99%